The Economic Impacts of Tourism on the Local Community of Bergville, Kwazulu Natal, South Africa - Mabaso, Simiso Lindokuhle (Journal of Economics and Behavioral Studies, 2015)
Tourism is playing an increasingly important role in the local and national economy. The outstanding beauty of the northern Drakensberg is a prime tourist attraction in KwaZulu-Natal, attracting a regular flow of tourists throughout the year (Okhahlamba Municipality, 2013). The primary objective of this research is to investigate whether the benefits of tourism that are supposed to be reaped by the local community of Bergville, exist. If so, what are these benefits? There might be people from the local community, who are working within the tourism sector, but what are the types of jobs that they do, their level of job-satisfaction, and the extent to which they are able to earn a living from employment within the tourism sector? Do they have the necessary skills and training to allow them to make a successful career within the tourism sector? The White Paper on the Development and Promotion of Tourism (DEAT, 1996), states that with any tourism development in the local communities, local people should be involved in the decision making. They should be trained if they lack the necessary skills required to participate in that development. All these issues are relevant to Bergville as the region has a lot of tourism development, and it is a place that integrates tourism and conservation.